(untitled) (Semiárida, 2025)
This study evaluated the abundance of soil macrofauna by functional groups under different maize (Zea mays L.) residue management practices (buried, burned, and no-tillage) during 2018 and 2020 in the Lower Negro River Valley, Argentina. Macrofauna (>2 mm) was extracted using soil monoliths from plots with three treatments and replicates per year. Organisms were classified as ecosystem engineers, detritivores, herbivores, and predators. Additionally, soil variables such as moisture, bulk density, pH, electrical conductivity, and organic matter fractions were measured. A total of 869 individuals were collected, distributed across 24 families and 10 orders. Ecosystem engineers were the most abundant group, followed by detritivore-herbivores and predators. The no-tillage treatment showed greater total abundance compared to other treatments. However, when considering interactions among functional groups, management, and year, engineers and predators exhibited lower abundance under no-tillage, though engineers significantly increased their abundance in this treatment between 2018 and 2020. Earthworms (Crassiclitellata) and isopods (Isopoda) were the most representative taxa. Soil pH negatively affected engineers, while electrical conductivity was positively associated with detritivores. After three consecutive cycles under these management practices, macrofauna abundance was not favored, and burned residue proved particularly detrimental. The proportions of functional groups and their temporal variation reflect the degree of soil disturbance and the availability and quality of trophic resources. In this context, no-till appears to be the management option with the least impact on soil macrofauna abundance.